Kandungan Isovlavon dan Vitamin E pada Formula Kombinasi Tepung Tempe dan Bekatul Untuk Memperbaiki Profil Lipid Darah - Sufiati Bintanah; Siti Fatimah Muis; Purwanto AP (Jurnal Gizi, 2018)
The prevalence of cardiovascular disease continues to increase as a result of dietary changes that have an impact on abnormal lipid profiles and oxidative stress. Efforts to improve lipid profiles byconsuming food contain antioxidant compounds that have the potential to improve blood lipid profiles. The aim of the study was to obtain a description of the content as an antioxidant in the formula of the combination of soybean tempeh flour with rice bran.Research method: This type of experimental research is to find out the most optimum antioxidant content of the formula. Making formulas, (1) yellow soybean tempeh flour + white bran flour, (2 black soybean tempeh flour + white bran flour (3) yellow soybean flour tempeh + red bran flour,(4) black soybean flour tempeh + red bran flour, with composition of 1: 1 and weighs 112 grams each, non-calorie sweetener 3 grams and food flavorings 3 grams, dissolved in cold water as muchas 250 cc, analysis of nutrients using the AOAC method, 2005 . Data analysis: Data obtained are averaged and displayed in table form, then compared between treatments. Results: The combination of YST + RBF with a composition of 1: 1 has a higher isovlavone content while the highest content of vitamin E is found in the combination of YST + WBF. Conclusion: There is sufficient isovlavone and tokoverol content from a combination of tempeh flour and bran to improve blood lipid profile.Keywords: Isoflavones, vitamin E, formula of tempeh and bran flour, blood lipid profile